The efficiency of international relations of regional higher educational institutions in a globalised context - M.M. Chunayev (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
In the context of globalisation, the purpose of regional higher education institutions is to provide access to education for people from all social strata and to facilitate their integration into the international arena. The primary objective was to achieve recognition and expansion of Azerbaijani higher education and regional higher education institutions in the global context. Additionally, Azerbaijani higher education aims to sign new cooperation agreements with foreign higher education institutions alongside existing collaborations. Methods of comparison, synthesis, induction, and deduction were employed in the study. The study confirmed that the international relations and strategic development plans of regional higher education institutions contribute to economic development. Furthermore, the programs implemented by these institutions have increased the number of foreign students, which improved the recognition of these regions abroad. As this is the first research study of its kind in the Republic of Azerbaijan, it will be valuable for domestic and international researchers. The conducted research, comparisons, and analyses facilitated the development of a comprehensive approach to learning theoretical concepts and models, which can be applied in teaching practices. Additionally, for foreign researchers, this study can be used as a resource for obtaining information about the regional higher education institutions in Azerbaijan, as well as their international relations, forming a foundation for further studies